Some of the obstacles facing young basketball players in the Republic of Yemen - ali mohmed alwffi, Brahim (sports creativity, 2025)
Some difficulties and barriers facing the beginner of basketball in Yemen Through intensive following of almost clubs that involve in basketball and my following the first degree tournament and youth , the researcher observed some problems facing some players which stand as a barrier for their advancement to higher levels . These problems are represented in financial , social and scientific aspects and other problems related to the management of clubs as some clubs delay the dues of the players including salaries and bonuses in addition to the lack of attention paid to the wounded players and lack of their rehabilitation to get them return to the playgrounds . The irregularity of tournament's schedule and irregularity of club in addition to the problems facing the club either financial or psychological ( change of coach ) . Thus , the researcher aims to investigate the problems and attempts to provide some solutions and recommendations for such problems . The researcher aims to : 1- Recognize the problems facing the beginners of basketball in Yemen . 2- Suggesting some solutions for such problems . The researcher used to the descriptive method in his surveying method for its fitness for the nature of the research , the sample of the study sample composed of the be gingers of basketball including ( 67) . The researcher has set up the following conclusions : 1- There are some problems related to the component trainer and training such as ( training is not exciting , players are stressful due to the nervousness of the coach , schedule of the training is not appropriate , lack of assessment for the performance of the players ) . 2- There are some problems related to the team component such as lack of cooperation of colleagues and bad treatment for players ) . 3- There are some problems related to the club : the club does not offer special lessons for the players , lack of adequate incentives and the club does not pay attention to the basketball ) . 4- There are some problems related to the psychology : lack of confidence of the physical abilities and skills of the players The researcher as set the following recommendations : 1- The coaches should pay attention to the training to be more interesting along with considering psychological aspects of the players and the time of training should be adequate for all players . 2- It is a must to increase sport awareness' through media means and practicing sport during all age stages 3- There must be cooperation between the club and school to provide solutions to compensate sportive students for the lessons missed due to their participation in the camps and matches. 4- There must set a system for the financial intensives by the club characterized by equality between various sport activities and paying more attention to the basketball. 5- There must be a specialist in psychological sport to assist the players in overcoming barriers facing them and decrease their level.